The Role of Activity-Based Budgeting in Evaluating Operational Performance: An Applied Study - Hammadi, Nermin Muin; Kadhim, Ezzaddin Hasan (Journal of Ecohumanism, 2025)
The research aims to evaluate operational performance in health service units using time-driving Activity-based budgeting(TDABB). The research problem is the weakness of evaluating operational performance in health service units that rely on traditional budgeting systems. The research was conducted at Al-Hakim General Hospital, Department of Surgery, Gynecology and Obstetrics. It was based on field visits, personal interviews, and collecting information from documents obtained from the hospital. Based on the researcher's findings, using an activity-based budgeting approach can lead to a more precise, transparent, and effective operational evaluation. Moreover, this approach can provide accurate information and reduce time and costs when implementing cost shadowing. Advanced cost accounting techniques were introduced to improve the government accounting system, including costing technology based on activity-based budgeting. This helped in determining the costs of the services provided. Additionally, the culture of change and development was promoted through modern technologies to control costs and effectively manage human resources, among other areas. As a result, the government was able to better control costs and ensure effective allocation of resources